Thermionic emission measurement of sintered lanthanum hexaboride discs and modelling of their solar energy conversion performance. Issue 14 (15th July 2021) - Bellucci, A.; Mastellone, M.; Girolami, M.; Serpente, V.; Sani, E.; Sciti, D.; Trucchi, D.M.
Abstract: Polycrystalline lanthanum hexaboride (LaB6 ) discs were sintered by hot pressing of commercial powders and successively polished, in order to investigate their thermionic emission capability. LaB6 samples presented values of work function in the range 2.55–2.61 eV. Discs with polished surface, independently from the composition and density, demonstrated to provide a Richardson constant around 45 A cm −2 K −2 . These results are promising for the use of sintered LaB6 discs in thermionic energy converters operating at temperatures in the 1400–1700 °C range. Moreover, since the properties of solar absorption and spectral selectivity of LaB6 make them appealing for the conversion of concentrated solar radiation, a modelling study to estimate the energy conversion efficiency was performed, aimed at identifying the proper engineering strategies able to make the resulting devices competitive for electrical conversion of concentrated solar radiation.